Vanadate oligomers interaction with phosphorylated myosi - Aureliano, M. (2014)
Using a myosin preparation containing endogenous myosin light-chain (LC2) kinase and phosphatase and calmodulin, i.e. near physiological ones, the interaction of vanadate oligomers with phosphorylated myosin was evaluated. Decavanadate or metavanadate solutions (2/15 mM totalvanadate) did not prevent the phosphorylation state of the regulatory myosin lightchain, as observed by urea-polyacrylamide gel electrophoresis. The relative order of line broadening upon protein addition, reflecting the interaction of thevanadate oligomers with phosphorylated myosin, was V10!/V4!/V 10/1 whereas, no changes were observed for monomericvanadate. In the presence of ATP, V1 signal was shifted upfield 2 ppm and became broadened, while V4 signal became narrowed. Moreover, a significant increase in myosin ATPase inhibition (60%) was observed when decameric vanadate species were present (1.4 mM). It is concluded that, under conditions near physiological ones, decamericvanadate differs fromvanadate oligomers present in metavanadate solutions due to its strong interaction with the phosphorylated enzyme and myosinATPaseinhibition.Besides,ATPdecreasestheaffinityofmyosinfortetravanadate,inducestheinteractionwithmonomeric vanadate, whereas it does not affect decamericvanadate interaction.